-
If x - 1 = 1 , then the value of { x4 - ( 1 / x2 ) } is x 3x2 + 5x - 3
-
-
1 4 -
1 2 -
3 4 - 0
-
Correct Option: B
Expression = | x4 - | ||
x2 | |||
3x2 + 5x - 3 |
Dividing numerator and denominator by x,
Expression = | ![]() | x3 - | ![]() | ||
x3 | |||||
3x + 5 - | |||||
x |
Expression = | ![]() | x3 - | ![]() | ||
x3 | |||||
3 | ![]() | x - | ![]() | + 5 | |
x |
Expression = | ![]() | x - | ![]() | 3 | + 3 | ![]() | x - | ![]() | ||
x | x | |||||||||
3 | ![]() | x - | ![]() | + 5 | ||||||
x |
Expression = | = | = | |||
3 + 5 | 8 | 2 |